Análise dos fatores sociodemográficos e ocupacionais em gestores e a sua relação com a síndrome de burnout - Serpa, Natália Pedroso (2021)
Throughout the years, the competitiveness among organizations is increasingly emphasized. Thus, the collaborators, as well as managers, are exposed to stress factors that, in the long-term, might result in burnout at work. The burnout syndrome is characterized as a reaction to the psychological tension to which professionals are subjected when performing their work tasks. In this context, we analyzed managers that work in retail in a city located in the central region of Rio Grande do Sul, where, using the Maslach Burnout Inventory and a questionnaire including socialdemographic (gender, age, marital status, education, parental status) and occupational (time in the job, place of work, management functions) factors, it was possible to relate them, through logistic regression, in order to search for a significant influence among these data. Regarding the importance of the study, we sought to perform a problematizing reading of the cases, aiming to bring improvements, not only for the organizations, but also for society, aiming to facilitate the companies’ decision-making and making the workplace more pleasant for managers and collaborators. Lastly, regarding the results obtained in this study, it is suggested that organizations create safer work environments, develop campaigns that encourage their managers to take care of mental health. It is also recommended to implement work gymnastics and activities that contribute to teamwork, in order to increase motivation and synergy among the teams of the retail sector of the city.